Gaya Kepemimpinan Ketua OSIM dalam Kegiatan Organisasi Siswa di MTs Negeri 1 Kota Palembang - Setyaningsih, Kris; Atika, Nyimas; Hartanti, Agda (Indo-MathEdu Intellectuals Journal, 2024)
This study aims to analyze the leadership style of the OSIM Chairperson in student organization activities and the impact of the leadership style on student organization activities at MTs Negeri 1 Kota Palembang. This is qualitative research utilizing interviews with a fieldwork approach. The research informants include the OSIM Chairperson, Vice Chairperson, OSIM Advisor, teachers, and students. Data collection techniques employed are observation, interviews, and documentation. Data processing and analysis are carried out in three stages: data reduction, data presentation, and conclusion drawing. Data validity was tested through triangulation methods, including source, technique, and time triangulation. The results show that the leadership style of the OSIM Chairperson in student organization activities at MTs Negeri 1 Kota Palembang is effective. This is evident in the active participation of the Chairperson in every organized activity. The Chairperson must exhibit fairness in decision-making through deliberation with members. This approach enables the Chairperson to motivate team members, fostering a sense of mutual assistance and emotional control among them.